Новые друзья Мишки Ушастика - Янчарский Чеслав (Книги - мои друзья, 2013)
Экземпляры: ф.15 (20151204) / Инвентарный номер: 52136 / Цена: 81.00. / Сис.шифр: И(4Пол) / Авт.знак: Я 66 / ГРНТИ: 17.82.93 / ББК: 84(4Пол)-44